Expert consensus on the combined investigation of ulnar neuropathy at the elbow using electrodiagnostic tests and nerve ultrasound. Issue 9 (September 2021) - Pelosi, Luciana; Arányi, Zsuzsanna; Beekman, Roy; Bland, Jeremy; Coraci, Daniele; Hobson-Webb, Lisa D.; Padua, Luca; Podnar, Simon; Simon, Neil; van Alfen, Nens; Verhamme, Camiel; Visser, Leo; et al.
Highlights: Expert consensus was sought to guide clinicians on the investigation of ulnar neuropathy at the elbow (UNE) using EDX and US. The experts agreed that all investigations of UNE should include both nerve conduction studies and US. US should include assessment of cross-sectional area and nerve mobility at the elbow, and imaging of the entire ulnar nerve. Abstract: The addition of ultrasound (US) to electrodiagnostic (EDX) tests can significantly enhance the accuracy of testing for ulnar neuropathy at the elbow (UNE). We aimed to obtain expert consensus to guide clinicians on the combined use of EDX and US in UNE investigation. Consensus was achieved using the Delphi method. Two consecutive anonymised questionnaires were submitted to 15 experts, who were asked to choose their level of agreement with each statement. Consensus was pre-defined as ≥ 80% rating agreement. The experts concluded that all investigations of UNE should include both nerve conduction studies and US. There was consensus that US should include cross-sectional area measurement and assessment of nerve mobility at the elbow, and that the entire ulnar nerve should be imaged. This study defined expert opinion on the 'core' techniques that should be used routinely in the UNE investigation using EDX and US. Areas with lack of consensus highlighted some controversial issues in the current use of these diagnostic modalities and the need for future research. This document is an initial step to guide clinicians on the combined investigation of UNE using EDX and US, to be regularly updated as new research emerges.